Direct combinatorial interaction between a herpes simplex virus regulatory protein and a cellular octamer-binding factor mediates specific induction of virus immediate-early gene expression. - O'Hare, P; Goding, C; Haigh, A (1988)
We provide evidence for a novel mechanism of transcriptional regulation in which the immediate-early (IE) transactivating protein of herpes simplex virus, Vmw65, is assembled into a specific DNA-binding complex together with a cellular octamer-binding factor (TRF). The assembly of Vmw65/TRF complex requires not only the core TRF recognition site, but also flanking sequences which are dispensable for TRF binding alone. We show from functional analyses that TRF binding by a motif is required but not sufficient to confer induction on a heterologous promoter, and it is the ability of the motif to allow TRF/Vmw65 complex assembly which correlates with functional activity. Thus, for the induction of HSV IE expression, Vmw65 forms a complex with TRF by recognition of the specific subset of appropriately flanked TRF binding sites present in each of the IE genes. This mechanism may provide a paradigm for the selective utilization of the same transcription factor in differential gene expression.